The Theory of Historiographic Metafiction as a Methodology for Examining the Postmodern Historical Novel - Hakobyan, Hasmik (Bulletin of Yerevan University B: Philology, 2026)
The article examines the theory of postmodern historical novel analysis, which was put forward by Canadian theorist Linda Hutcheon. In 1988, the theorist proposed the term "historiographic metafiction" as an effective way to examine a novel that combines history and fiction, revealing history as a constructed narrative rather than absolute truth. Historiographic metafiction combines elements of the historical novel and metafiction. Works of this type often question the objectivity of the presentation of history, emphasizing that history is textual, constructed through narratives, and subject to subjective interpretations. Artistic autonomy is maintained, and at the same time the text is returned to the "world", but not to "ordinary reality", but to the "world" of discourse, to the "world" of texts and intertexts. This type of novel is self-analytical, accepting its own artistic nature, questioning historical truth and the writing of history. It uses intertextual, parodic, and language-game techniques to examine how historical narratives are formed and to challenge traditional distinctions between history and fiction. The study is relevant in Armenian literary studies, as the theory proposed by L. Hutcheon can become an important tool in the examination of post-independence, particularly post-war, historical-themed novels of a postmodernist nature.